Navigating the nutritional paradox: The impact of sustainable development targets on childhood wasting and overweight prevalence - Ijaiya, MA; Anjorin, S; Uthman, OA (Public Library of Science, 2024)
In 2015, the United Nations member states endorsed the 2030 Agenda for Sustainable Development to chart a path towards a better future for all. Childhood malnutrition, particularly wasting, remains a critical global health challenge, disproportionately affecting children under five in low- and middle-income countries. This study evaluates the impact of achieving selected Sustainable Development Goal (SDG) targets on reducing childhood malnutrition, with a specific focus on wasting and overweight. Utilizing multi-country DHS datasets, this study analyzed data from 138,782 children under five across 27 countries, nested within 13,788 neighborhoods. We simulated the predicted prevalence of wasting and overweight as selected SDG-related health inputs and determinant indicators reached their target values. Our findings reveal a baseline prevalence of 6.3% for wasting and 4.3% for overweight among the children studied. Progress towards the SDGs can potentially decrease wasting prevalence by a quarter (25%), translating to a reduction from 6.3% to 4.7%. This significant reduction in wasting is more pronounced in rural areas (29%) than in urban settings (7%). Conversely, a 14% increase in overweight prevalence was observed, with rural areas experiencing a higher rise (15%) than urban areas (13%). The study also highlighted variations in access to safe sanitation, improved water sources, healthcare services, income, maternal employment, and education levels, underscoring the complex interplay between these factors and malnutrition outcomes. Notably, the reduction in wasting prevalence was mainly attributable to input determinants rather than direct health inputs, suggesting the importance of broader socioeconomic factors in combating malnutrition. Achieving SDG targets presents a significant opportunity to mitigate wasting, particularly in rural communities. However, the uneven distribution of improvements underscores the need for targeted interventions in less affected areas. The concurrent rise in overweight prevalence, points to the emerging challenge of addressing the dual burden of malnutrition. This necessitates integrated, multi-sectoral strategies considering the diverse health determinants and nutritional status.